Peningkatan Pembelajaran Seni Tari Materi Gerak Tari Alam Semesta Melalui Pendekatan SAVI - Dewi, Wulan Kusuma (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this research is to improve the quality of learning, especially the students activity learning and learning result on materr motion of the nature of dance learning applying SAVI (Somatic, Auditory, Visual, Intellectual) approach in grade II elementary school. This research is Classroom Action Research with two cycles collaborated with the dance teacher of 2nd grade, with each cycle consisting of two meetings. The stages of each cycle are planning, action, observing, and reflection. Based on the analysis of data, the average scores of student learning from 83,61 on first cycle increased become 89,84 in second cycle. The tally showed an increase in the learning from first cycle to second cycle. Therefore, it can be concluced that the implementation of a SAVI approach can increased the matter of motion of the nature in dance learning on 2nd grade of Sumilir 1 Elementary School District of Purbalingga.